2002
DOI: 10.3354/dao052109
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Flavobacterium psychrophilum in fish-farming environments

Abstract: Occurrence of Flavobacterium psychrophilum in fish farms and fish-farming environments was studied using agar plate cultivation,the immunoflourescence antibody technique (IFAT) and nested PCR. Characteristics of 64 F. psychrophilum isolates from rainbow trout Oncorhynchus mykiss, fish farm rearing water, ovarian fluid and wild fish were serotyped, ribotyped and compared biochemically. Virulence of F. psychrophilum isolates from different sources was compared by injection into rainbow trout. Additionally, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
85
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 28 publications
11
85
0
1
Order By: Relevance
“…Previous studies showed that F. psychrophilum is transmitted both horizontally (Madsen and Dalsgaard, 1999;Garcia et al, 2000;Madetoja et al, 2000) and vertically (Brown et al, 1997;Kumagai et al, 2000;Cipriano, 2005). Furthermore, F. psychrophilum has been detected in ovarian fluid, skin mucous, and internal organs of salmonid fish with no disease signs (Holt et al, 1993;Madetoja et al, 2002;Madsen et al, 2005). The presence of F. psychrophilum with high frequency would be potential source of infection to salmonid fish including chum salmon adult female and fry because the pathogen is virulent to salmonid fish juveniles as suggested in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that F. psychrophilum is transmitted both horizontally (Madsen and Dalsgaard, 1999;Garcia et al, 2000;Madetoja et al, 2000) and vertically (Brown et al, 1997;Kumagai et al, 2000;Cipriano, 2005). Furthermore, F. psychrophilum has been detected in ovarian fluid, skin mucous, and internal organs of salmonid fish with no disease signs (Holt et al, 1993;Madetoja et al, 2002;Madsen et al, 2005). The presence of F. psychrophilum with high frequency would be potential source of infection to salmonid fish including chum salmon adult female and fry because the pathogen is virulent to salmonid fish juveniles as suggested in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Simply by being slightly more hydrated, the fluid could have a markedly lower viscoelasticity and be readily penetrable by motile bacteria [82]. In fact, in challenge experiments with bacteria, removal of mucus/epidermal cells increased the cumulative mortality in salmonids compared to undamaged fishes [266,267].…”
Section: Fish Skin Mucosal Immunologymentioning
confidence: 99%
“…The bacterial cells were biochemically characterized using tests suitable for Flavobacterium psychrophilum, including hydrolysis of starch (Pacha 1968), casein (Bernardet 1989), gelatin, esculin (Madetoja et al 2001) and elastin, production of catalase (Madetoja et al 2002), absorption of Congo red (Ishiguro et al 1985), presence of flexirubin-type pigments ) and cytochrome oxidase activity using the BBL TM Oxidase Reagent Droppers (BD). The enzymatic activity of the bacterial cells was also tested using a semi-quantitative micromethod, API ZYM (bioMérieux), in which the strips were incubated for 17 to 19 h at 15°C.…”
Section: Bacterial Isolates and Growth Conditions Thementioning
confidence: 99%